Update on surgical management of complex macular holes: a review - Mohd. Asyraaf, Abdul Kadir; Lik, Thai Lim (BMC part of Springer Nature., 2021)
Abstract Modern surgical interventions efectively treat macular holes (MHs) more than 90%. Current surgical treatment for MHs is pars plana vitrectomy with epiretinal membrane, internal limiting membrane (ILM) peeling, gas endotam‑ ponade, and prone posturing postoperatively. However, a small subset of MHs imposes challenges to surgeons and frustrations on patients. A narrative review was performed on the surgical treatment of challenging MHs including large and extra-large MHs, myopic MHs with or without retinal detachment, and chronic and refractory MHs. There are robust data supporting inverted ILM fap as the frst-line treatment for large idiopathic MHs and certain secondary MHs including myopic MHs. In addition, several studies had shown that ILM fap manipulations in combination with surgical adjuncts increase surgical success, especially in difcult MHs. Even in eyes with limited ILM, surgical options included autologous retinal graft, human amniotic membrane, and creation of a distal ILM fap that can assist in MH closure even though the functional outcome may be afected by the MH chronicity. Despite relative success anatomi‑ cally and visually after each technique, most techniques require a long-term study to analyze their safety profle and to establish any morphological changes of the MH plug in the closed MHs. Keywords: Macular hole, Vitrectomy, Vitreoretinal disease, Internal limiting membrane peeling